Pengembangan Sistem Informasi Akuntansi Yang Efisien Dalam Meningkatkan Operasional Perusahaan Di PT Malindo Feedmill TBK Di Gresik - Rosaria Rudeng; Hwihanus Hwihanus (Universitas 45 Surabaya, 2024)
The purpose of this research is to improve the development of accounting information systems add value or company competitiveness,find out information collection and the result of information obtained from the PT Malindo Feedmill Tbk. The type of research carried out was qualitative research with primary data sources obtained from PT Malindo Feedmill in 2018 – 2019. The population in this research were employees from PT Malindo Feedmill Tbk. In analyzing,researchers used data collection techniques by observation,interview and literature study. The result of this research is an Accountancy Information System that is efficient in improving company operations wheren the descriptive decision making variable is good because it has an average of 3,83